Correlates of Unwanted Pregnancy among Pregnant Women attending Medical and Health Centers in Semnan, Iran - H Sanaie Nasab; H Rashidi Jahan; R Tavakoli; HR Tavakoli; F Amin Shokravi (Tehran University of Medical Sciences, 2009)
Background & Aim: Unwanted pregnancy is one of the most important causes of mother and child mortality. It may end up to illegal abortion and result in inevitable physical and psychological consequences. This study aimed to determine the correlates of unwanted pregnancy among pregnant women attending medical and health centers in Semnan. Methods & Materials: In this cross-sectional study, we recruited 229 pregnant women using random sampling. Women with at least one alive child were recruited. Data were gathered using a questionnaire and analyzed using descriptive; analytical statistical tests. Results: The mean age was 30.7. The mean age at marriage was 19.7. Of all women, 32.3% had unwanted pregnancy. The results showed that there were significant relationships between age of marriage (P<0.05), current age of women (P<0.05), level of education (P<0.05), No. of children (P<0.01), employment (P<0.05), and income (P<0.01) with unwanted pregnancy. Conclusion: The prevalence rate of unwanted pregnancy was high in the studied population. Educational programs regarding correct methods of contraceptive usages are required.